Young Investors' Interest in Mutual Fund Investment - Ngurah Yudikaswira, I Gusti (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
The investment sector has an important role in a country's economy, especially in developing countries like Indonesia. Without good investment prospects, it is difficult to develop economies of scale that will bring prosperity to developing countries. This study aims to find out what are the backgrounds of young investors who are interested in investing in mutual funds in the Seeds and Bareksa applications. Researchers used a qualitative approach with a descriptive method as a research method. The use of the Seeds and Bareksa applications in mutual fund investments has various promotions that increase investor interest in investing in these applications. Promotions are offered such as cashback and discounts when investing and also if you can invite colleagues to join the application and make investments. Many young investors choose the Seeds application over Bareksa in investing in mutual funds online, namely because the ease of features in the application provided by Seeds are easier for young investors to understand.